Influence Motor Cycle Density on Noise Sound at the Highway - Syaiful, Syaiful; Shinta Aminda, Renea; Afrianto, Yuggo (ASTONJADRO, 2023)
Bogor Regency is a buffer zone for the city of Jakarta. Bogor Regency is directly adjacent to the north with DKI Jakarta and Bekasi City and Depok City. The two cities are satellite cities directly adjacent to Jakarta. In 2017 and 2018, the addition of roads in Indonesia was only less than 0.1% -0.2%/year, while the growth of motorized vehicles was more than 10%/year. This is very disproportionate to the addition of roads in our country. Based on the study above, research on motorized vehicles was carried out in front of the Nurul Hidayah Mosque, which is located on Jl. Salabenda-Semplak, Bogor Regency. The density of motorcycles, private cars, public transport cars and freight cars has a significant effect on noise. From all analysis calculations, the largest equation is obtained on the third day of the second point of the study SLM2, with a contribution of 22.12%. The following calculation is obtained, y = 54.01 + 0.04x1 + 0.32x2 – 0.22x3 + 0.12x4. This means that if there is no decrease in the density of motorbikes, the noise level in SLM2 is 54.021 dBA. The density of motorbikes, private cars, public transport cars and freight cars also has a significant effect on noise, the second largest equation is obtained on the fourth day of research at the third point with a contribution of 21.24%. The calculation of the equation below is obtained, y = 55.02 + 0.03x1 – 0.07x2 + 0.02x3 – 0.01x4. The meaning of the above equation is that if there is an increase in the density of motorcycles and public transport cars, the noise in SLM3 is 55,021 dBA.